"Delicate, petite & other things I'll never be": trans-punk anthems and love songs. (2nd January 2020) - Schott, Gareth
ABSTRACT: Punk's dogged durability continues to be driven by a communal ethos that once embodied inclusivity, resistance, challenge, and transformation. The precipitous absorption and integration of punk into the mainstream ran the risk of undermining the authenticity of its rebellion, DIY principles, and sub-cultural inimitability. Yet, in emerging from the underground punk has continued to provide a counter-normative framework and aesthetic. The ethos that underpinned first-wave punk is evident today in punk's ongoing engagement with queer politics and persistent illustrations of gender fluidity. This article examines an articulation of "transgender as punk" focusing on the example of Laura Jane Grace, lead singer of U.S. anarcho-punk band Against Me!, who came out as transgender five albums into her public life as an established punk musician. Punk has time and again served as a site for making visible and verbalising discordant experiences, which Grace has accessed to document her complex and troubled personal intercessions, transgender realities, and their uncertain future.